2012
DOI: 10.5005/jp-journals-10024-1245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Knowledge and Experience among Oral and Maxillofacial Surgeons about Cardiopulmonary Resuscitation

Abstract: Objective This study was undertaken to assess the level knowledge and experience about CPR among oral and maxillofacial surgeons. Materials and methods In a cross-sectional study, a total of 96 professionals (31-PGs, 65-MDS staff) were surveyed using a self-administered structured questionnaire pretested through a pilot survey. The data was analyzed using the SPSS version 15.0. The Student's t-test and ANOVA test were used as test of significance. The level of significance was set at p ≤ 0.05. Results In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…There was no significant difference in various factors (e.g., previously receiving CPR training, practicing orotracheal intubation, and using a defibrillator) that could have affected the level of correct answers of the dentists who participated in the survey. The results of this study demonstrate that dentistry students in Turkey have insufficient knowledge and experience of CPR, in common with findings in many other countries [8][9][10][11].…”
Section: Discussionsupporting
confidence: 69%
“…There was no significant difference in various factors (e.g., previously receiving CPR training, practicing orotracheal intubation, and using a defibrillator) that could have affected the level of correct answers of the dentists who participated in the survey. The results of this study demonstrate that dentistry students in Turkey have insufficient knowledge and experience of CPR, in common with findings in many other countries [8][9][10][11].…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, our study showed that younger aged participants with lower career hierarchy and less than 10 years' clinical experience had significantly higher knowledge scores in comparison to others. On the contrary, it was noticed in other studies [19,20] that subjects with more than 10 years' clinical experience had better CPR knowledge compared to the less experienced ones. This finding overemphasizes the importance of CPR training.…”
Section: Discussionmentioning
confidence: 71%
“…Previous research has investigated the attitude, knowledge, and practice of CPR amongst doctors, nurses, lifeguards, paramedics, dentists, radiographers, physiotherapists, and dental and medical students [17][18][19][20][21][22][23][24][25][26][27][28]. Furthermore, international research into health professionals' attitudes, beliefs, and knowledge of CPR has led to changes in training and improvement in CPR skills and practice [25,29,30].…”
Section: Introductionmentioning
confidence: 99%